MR microscopy of the human fetal upper extremity – a proof-of-principle study. Issue 1 (December 2016) - Langner, Inga; Stahnke, Thomas; Stachs, Oliver; Lindner, Tobias; Kühn, Jens-Peter; Kim, Simon; Wree, Andreas; Langner, Soenke
Abstract Background Current knowledge of the human fetal and embryonic development relies on early descriptive studies of humans and from experimental studies of laboratory animals and embryos. Taking the upper extremity as an example, this study explores the potential of magnetic resonance microscopy (MRM) for the assessment of the development of the fetal upper extremity and discusses its correlation with histological findings. Methods Ex vivo MRM at 7.1 T (Clin Scan, Bruker Biospin, Germany) was performed in 10 human specimens at 8 to 12 weeks of gestational age (GA). In-plane resolution was 20 μm with a slice thickness of 70 μm. MRM was followed by histological work-up of the specimens. MRM images were then correlated with conventional histology with a focus on the presence of chondrification and ossification. Results Ossification of the upper human extremity is detectable at 8 weeks GA in the humerus and the long bones of the forearm. There is excellent correlation for location and size of ossification between MRM and conventional histology. MRM imaging is in accordance with historical studies. Conclusion Ex vivo MRM for the non-invasive assessment of the embryonic and fetal development of the upper human extremity is feasible. It may provide an accurate complementary tool for the evaluation of embryological development.